Analysis of Han Characters Learning in Senior High School in Cirebon - Simin, Natasha; Sutandi, Septerianie (Universitas Dian Nuswantoro, 2023)
Along with Mandarin, which has become the second international language, learning Mandarin is increasingly considered very important. However, this trend has not run optimally in Cirebon; since the COVID-19 pandemic, several schools have eliminated Mandarin lessons. Apart from the lack of teaching staff for Mandarin in Cirebon, this condition is also caused by several problems in learning Mandarin in schools, one of which is learning Han characters. This research analyzes how Han characters are taught in a high school in Cirebon City and uses a qualitative descriptive approach with data collection techniques like observation, questionnaires, and quizzes. This study aims to solve the problem of learning Han characters and encourage the development of Mandarin language learning in Indonesia, especially in Cirebon. The study found that teaching staff, learning methods, and materials were the main problems in learning Han characters at the research location. The implications of the results of this study can be used as a reference for stakeholders, such as schools and the government, to pay attention to the quality of Mandarin language learning, especially in providing quality teaching staff and using appropriate learning methods and materials.